Socio-economic factors do also matter: comments on the article "can climatic factors explain the differences in COVID-19 incidence and severity across the SPANISH regions?: an ecological study" - Pedro Muñoz Cacho; José L. Hernández; Marcos López-Hoyos; Víctor M. Martínez-Taboada (BMC, 2021)
Abstract Phosri et al., commented on our previous study about the influence of climate variables at the beginning of the SARS-CoV-2 pandemic in Spain. They showed the impact of the association of gross domestic product (GDP) with the cumulative COVID-19 incidence per 105 inhabitants in our country and the rise of several methodologic issues. Here we discussed the main advantages and disadvantages of ecological studies and we advocate to test the hypothesis created in this type of studies using individual-level research designs.